TO THE PROBLEM OF UNDERSTANDING NON-PERSONAL PROPERTY RELATIONSHIP REGARDING CONFIDENTIAL INFORMATION IN THE FIELD OF HEALTH CARE - Khodakivskyi, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of this article is to identify the norms of the current civil legislation of Ukraine, which are designed to regulate non-property relations regarding confidential information in the field of health care, which are not of a personal nature. The methodological basis of the research is general scientific and special methods of scientific knowledge. The use of these methods made it possible to identify and describe the norms of the current civil legislation of Ukraine, which are designed to regulate non-property relations regarding confidential information in the field of health care, which are not of a personal nature. Results: not all civil rights and obligations that have a non-property nature are personal. Using the example of relevant norms of the current civil legislation, it was demonstrated that some legal relations in the field of health care are non-personal non-property, which means that the norms of the current civil legislation of Ukraine, in addition to personal non-property relations, can also regulate non-personal non-property relations. Discussion: in order for impersonal non-property relations to be considered as personal property relations, we use the example of Art. 1 of the Civil Code of Ukraine, should be interpreted based not on its literal understanding, but on the doctrinal and/or judicial basis. That is, to actually recognize the doctrine and judicial practice as a source of civil law. However, this approach then goes against the legal concept of civil law of Ukraine, violates the principles of legal certainty and the rule of law. Therefore, in order to avoid such violations, non-personal non-property relations should be defined in the subject of the civil law of Ukraine, i.e. in Part 1 of Art. 1 of the Central Committee of Ukraine. Moreover, the science of civil law and judicial practice traditionally consider them civil. This would contribute to the legal certainty and quality of our civil legislation.